The management of liquidity risk in islamic banks: the evidence from Malaysia / Nur Fatehah Hasyimah Hassim - Hassim, Nur Fatehah Hasyimah (Faculty of Business Management, 2017)
The study is about how liquidity influencing the Islamic banks in Malaysia. The study evaluates the liquidity of a bank by using their total asset, return on asset and capital requirement therefore liquidity management could raise funds to meet the demands of depositors and borrowers at any times with satisfactory price. The result of this study is, it showed negative significant relationship between return on equity and capital requirement toward the liquidity of Islamic banks, meanwhile for return on asset and total asset it show positive significant toward the liquidity Islamic banks. As for the sample of this study, it comprises of 100 observations each for the independent and dependent variables on an annually basis over ten years period from 2006 to 2015 from 10 Islamic bank institutions. The methodology used in this study is the Multiple Linear Regression and Correlation analysis with panel data that are gathered from Bank scope at UiTM library website. A software package called E-views will be used in finding and analyzing the data. In order to investigating the factor that influences liquidity on Islamic banks in Malaysia.